2012
DOI: 10.1016/j.econlet.2012.05.026
|View full text |Cite
|
Sign up to set email alerts
|

On international spillovers

Abstract: This study investigates the role of international spillovers in generating productivity gains for a panel of 24 OECD countries during the period between 1971-2004. We use recent techniques developed in a common factor framework to characterize the global interdependence implied by international spillovers and the diusion mechanisms involved. Consistent with some recent studies in this eld, the evidence suggests that there are substantial crosscountry spillovers mainly related to R&D and human capital variables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Large trade relationships are certainly important for international knowledge transmission, but knowledge 1 Several scholars have refined Coe and Helpman's (1995) seminal analysis along several directions, ranging from the econometric technique and the data to the level of disaggregation and the composition of the trade flows, while preserving their approach (e.g. Engelbrecht, 1997;Lichtenberg and van Pottelsberghe de la Potterie, 1998;Xu and Wang, 1999;Lumenga-Neso et al, 2005;Madsen, 2007;Coe et al, 2009;Bianco and Niang, 2012;Fracasso and Vittucci Marzetti, 2013). We refer to Keller (2004) for a review of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Large trade relationships are certainly important for international knowledge transmission, but knowledge 1 Several scholars have refined Coe and Helpman's (1995) seminal analysis along several directions, ranging from the econometric technique and the data to the level of disaggregation and the composition of the trade flows, while preserving their approach (e.g. Engelbrecht, 1997;Lichtenberg and van Pottelsberghe de la Potterie, 1998;Xu and Wang, 1999;Lumenga-Neso et al, 2005;Madsen, 2007;Coe et al, 2009;Bianco and Niang, 2012;Fracasso and Vittucci Marzetti, 2013). We refer to Keller (2004) for a review of the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Bianco and Niang (2012) attempt to extend the analysis of Coe et al . (2009) by using the panel data of 24 OECD countries over the period 1971–2004.…”
Section: Drivers Of Mfp: a Thematic Review Of Literaturementioning
confidence: 99%
“…Similarly, Bianco and Niang (2012) attempt to extend the analysis of Coe et al (2009) by using the panel data of 24 OECD countries over the period 1971-2004. TFP is used as a dependent variable, whereas R&D capital stock 16 and human capital are used as principal exogenous variables.…”
Section: Domestic and Foreign Randd Spilloversmentioning
confidence: 99%
“…Bianco and Niang (2012) analysed the role of international spillovers in generating gains for a panel of 24 OECD countries. They found that substantial cross-country spillovers occur, mainly relating to R&D and human capital variables, which contribute significantly to productivity.…”
Section: Theoretical Framework: Ertur and Koch's Multi-country Schumpmentioning
confidence: 99%